PENGEMBANGAN PROGRAM EDUKASI KEBIDANAN UNTUK REMAJA TENTANG KESEHATAN REPRODUKSI - Rani Fitriani; Eva Mesi Setiana (Stikes Yarsi Mataram, 2023)
Comprehensive sexual education for adolescents is important in efforts to improve their reproductive health. This article presents community service conducted at MA Plus Walisongo, North Lampung, with the aim of developing a midwifery education program that focuses on adolescent reproductive health. Through outreach, counseling, and training, this program aims to increase youth's knowledge and awareness about reproductive anatomy, menstruation, contraception, sexually transmitted infections, pregnancy, and wise decisions in sexual life. The method used involved a comprehensive sex education module, group discussions, and question and answer sessions. The results of this dedication show an increase in youth's knowledge and understanding of reproductive health, as well as increased awareness of safe and responsible reproductive health practices. This program has also succeeded in reducing the risk of teenage pregnancy, unsafe abortion, and transmission of sexually transmitted diseases. In conclusion, this community service makes a positive contribution in improving adolescent reproductive health at MA Plus Walisongo, North Lampung, and emphasizes the importance of accurate, scientific and dignified sexual education as a solution to addressing adolescent reproductive health problems.